Decoder-Generated Miscommunication as a Politeness Strategy on 2go Interactive Messenger - Oyadiji, Olushola Ebenezer (Àgídìgbo: ABUAD Journal of the Humanities, 2017)
Politeness as a vital tool in human communication has been widely studied by linguists who sought to explicate its use in sustaining rapport and its perception in the patterning of human interaction. This paper furthers that line of enquiry by seeking to extend the application of existing politeness theories to the relatively new computer-mediated-communication domain of 2go. It solicited and subjected samples of chats from 2go interactions, which display a potential for flame war, to qualitative analysis based on an eclectic framework suffused with insights from the Face-negotiation theory, Lim and Bowers’ model of FaceTheory, Spencer-Oatey and Jiang’s Sociopragmatic Interactional Principles as well as Shea’s Netiquette. It found that ‘chatters’ on 2go achieve politeness and rapport management through the deliberate use of miscommunication generated by the decoders who save the conversations from degenerating into banters in line with the context negotiated in the chat. Chatters avoid countering with threats to others’ face by avoiding autonomy face-threatening moves. They also adopt a desired interpretation from the alternatives in the encoders’ messages, thus using avoidance or misconstruction to reject and mitigate impoliteness while emoticons ameliorate face threats. Politeness in the chats thus relies on the use of the strategies of avoidance, misinterpretation, distortion and FTA mitigation through emoticons. Miscommunication is a key strategy of politeness on 2go chat. This strategy is deserving of intense study in order to further determine its relevance to rapport management in other virtual communities, as well as other domains of human interaction.